High detection rate of adenomas in familial colorectal cancer. Issue 1 (9th September 2010) - van der Meulen-de Jong, A E; Morreau, H; Becx, M C J M; Crobach, L F S J; Haastert, M van; Hove, W R ten; Kleibeuker, J H; Meijssen, M A C; Nagengast, F M; Rijk, M C M; Salemans, J M J I; Stronkhorst, A; et al.
Abstract : Background and aims: Subjects with one first-degree relative (FDR) with colorectal cancer (CRC) <50 years old or two FDRs with CRC have an increased risk for CRC (RR 4–6). Current guidelines recommend colonoscopic surveillance of such families. However, information about the yield of surveillance is limited. The aim of the present study was to evaluate the outcome of surveillance and to identify risk factors for the development of adenomas. Patients and methods: Subjects were included if they fulfilled the following criteria: asymptomatic subjects aged between 45 and 65 years, with one FDR with CRC <50 years old (group A) or two FDRs with CRC diagnosed at any age (group B). Subjects with a personal history of inflammatory bowel disease or colorectal surgery were excluded. Results: A total of 551 subjects (242 male) met the selection criteria. Ninety-five subjects with a previous colonoscopy were excluded. Two of 456 remaining subjects (0.4%) were found to have a colorectal tumour (one CRC and one carcinoid). Adenomas were detected in 85 (18.6%) and adenomas with advanced pathology in 37 subjects (8.1%). 30 subjects (6.6%) had multiple (>1) adenomas. Men were more often found to have an adenoma than women (24% vs 14.3%; p=0.01). Adenomas were more frequent in group B compared with group A (22.0% vs 15.6%; p=0.09). Conclusion: The yield of colonoscopic surveillance in familial CRC is substantially higher than the yield of screening reported for the general population.